Direct Alkynylation of Carbonyl Compounds Using an Efficient Catalytic System: Triisopropylsilanol/KOH - Wen, Yuanjie; Wang, Yurou; Liang, Jianqing; Yan, Yaolong; Chen, Weifeng (Synlett, 2025)
The first triisopropylsilanol/KOH-catalyzed direct alkynylation of carbonyl compounds to access propargylic alcohols was achieved. This approach is particularly simple and operates under mild conditions. Moreover, the catalytic system exhibits a wide tolerance for various substrates, including aromatic aldehydes and aromatic acetylenes, giving 1,3-diarylpropargyl alcohols with yields exceeding 88%, avoiding the usual formation of chalcone derivatives or polymers.
Keywords: alkynylation; triisopropylsilanol; propargylic alcohol; KOH; carbonyl compounds